Estimation of Renal Function for Antibiotic Dosing Decision - Fésüs, Adina; Szilágyi, Zsanett; Khabbaz, Ghazal Mohammadi; Vaskó, Attila (De Remediis, 2026)
Background: Accurate renal function assessment is essential for appropriate antibiotic dosing in critically ill patients. However, different estimation equations may yield discrepant results, potentially leading to dosing errors and suboptimal clinical outcomes.Objectives: To compare antibiotic dosing appropriateness based on renal function estimated using Cockcroft–Gault (CG), MDRD, and CKD-EPI equations, and to evaluate associated clinical outcomes in ICU patients with pneumonia-associated sepsis.Methods: In this single-center retrospective observational study, 229 adult ICU patients were included. Renal function was estimated using CG, MDRD, and CKD-EPI equations. Antibiotic dosing was classified as appropriate or inappropriate according to SPC and local guidelines. Clinical outcomes, including 30-day mortality/survival, and length of stay (LOS) were analyzed.Results: Based on CKD-EPI and MDRD, 57.2% and 55.5% of patients received appropriate dosing, respectively. However, 7.4% of patients considered appropriately dosed by these equations were reclassified as inappropriately dosed using CG. While mean renal function values were similar across equations (~67 mL/min), median values differed by approximately 20 mL/min (CG: 74 mL/min vs. CKD-EPI/MDRD: 52 and 50 mL/min), leading to clinically relevant reclassification. Inappropriate dosing was associated with older age and higher comorbidity burden. Piperacillin/tazobactam was most frequently underdosed, whereas clarithromycin, cefepime, and amikacin were commonly overdosed. Patients with inappropriate dosing had longer hospital LOS (median 14 vs. 11 days) and ICU-LOS (9 vs. 6 days), and showed worse survival, although 30-day mortality differences were not significant.Conclusions: The choice of renal function equation significantly impacts antibiotic dosing decisions. CG-based assessment may better identify dosing inaccuracies, and inappropriate dosing is associated with worse clinical outcomes. Optimized, individualized dosing strategies are warranted in critically ill patients.